Current evidence for anesthesia management during endovascular stroke therapy: updated systematic review and meta-analysis. (15th June 2018) - Goyal, Nitin; Malhotra, Konark; Ishfaq, Muhammad F; Tsivgoulis, Georgios; Nickele, Christopher; Hoit, Daniel; Arthur, Adam S; Alexandrov, Andrei V; Elijovich, Lucas
Abstract : Introduction: Debate continues about the optimal anesthetic management for patients undergoing endovascular treatment (ET) of acute ischemic stroke due to emergent large vessel occlusion. Objective: To compare, using current evidence, the clinical outcomes and procedural characteristics among patients undergoing general anesthesia (GA) and local or monitored anesthesia (non-GA). Methods: We performed a systematic review and meta-analysis of all available studies that involved the use of stent retrievers for ET (stentriever group). Additionally, we included studies that were published in 2015 and later, and compared the clinical outcomes among the studies using stentrievers or no stentrievers (pre-stentriever group). Outcome variables included functional independence (FI; modified Rankin Scale scores of 0–2), symptomatic hemorrhage, mortality, procedure duration, and vascular and respiratory complications. We calculated pooled odds ratios and 95% CIs using random-effects models. Results: Sixteen studies (three randomized controlled clinical trials (RCTs) and 13 non-randomized studies) were identified comprising 5836 patients. Although non-GA was associated with higher odds of 3-month FI (OR=1.57; 95% CI 1.17 to 2.10; P=0.003) and lower odds of 3-month mortality (OR=0.62; 95% CI 0.47 to 0.82; P=0.0006, substantial heterogeneity was noted across included trials. Sensitivity analyses of RCTs showed that non-GA was inversely associated with FI (OR=0.55; 95% CI 0.34 to 0.89; P=0.01; I 2 =15%), while no association was noted with mortality (OR=1.36; 95% CI 0.79 to 2.34; P=0.27; I 2 =0%). Conclusion: Our updated meta-analysis demonstrates favorable results with non-GA, probably owing to inclusion of non-randomized studies. Recent single-center RCTs indicate that GA is associated with higher odds of FI at 3 months, while other outcomes are similar between the two groups.